PENGELOLAAN OBJEK WISATA TANGSI BELANDA OLEH DINAS PARIWISATA KABUPATEN SIAK PROVINSI RIAU TAHUN 2020 - Kartika, Putri Dewi; ', Wazni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
The background to this research is that the current state of the Dutch Tangsi tourist attraction is in a bad condition in terms of buildings, with some parts of the roof being fragile and infrastructure problems such as public toilets for tourists and a lack of facilities that can satisfy tourists. The aim of this research is to determine the management of the Dutch Tangsi tourist attraction. The type of research in this thesis is a qualitative descriptive research type where descriptive data is answered by research informants and analyzed by the author. To find out the management of the Dutch Tangsi tourist attraction in Siak Regency, in this research the author needs primary data in the form of interviews and direct observations in the field then secondary data in the form of documents related to the management of the tourist attraction carried out.The data collection methods that the author uses in this research are observation, interview and documentation techniques. There were 9 informants for this research The results of research conducted by researchers on the management of the Dutch Tangsi tourist attraction by the Siak Regency Tourism and Culture Office are quite good, but there are still parts of the management of the Dutch Tangsi tourist attraction that are not running according to the planned activities Keywords: Management, Dutch Tangsi, Siak Tourism Office